2021
DOI: 10.1177/00220221211025739
|View full text |Cite
|
Sign up to set email alerts
|

Self-Interest Bias in the COVID-19 Pandemic: A Cross-Cultural Comparison between the United States and China

Abstract: In the global crisis of the COVID-19 pandemic, many countries attempt to enforce new social norms to prevent the further spread of the coronavirus. A key to the success of these measures is the individual adherence to norms that are collectively beneficial to contain the spread of the pandemic. However, individuals’ self-interest bias (i.e., the prevalent tendency to license own but not others’ self-serving acts or norm violations) can pose a challenge to the success of such measures. The current research exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 50 publications
(83 reference statements)
2
12
0
Order By: Relevance
“…Previous studies suggested a number of factors that influence the degree to which people in different societies supported or rejected COVID-19 pandemic-related health behaviors, including selfinterest, pro-sociality, religiosity, conspiracy beliefs, trust, national identification, perceived effectiveness, and quality of institutions (7)(8)(9)(10)(11)(12)(13)(14). In this paper, we argue that in order to understand why people support or oppose certain measures, it is crucial to understand (I) which individuals, groups, social movements, or organizations (referred to as 'protagonists' in the following) people identify as relevant and (II) how they are evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested a number of factors that influence the degree to which people in different societies supported or rejected COVID-19 pandemic-related health behaviors, including selfinterest, pro-sociality, religiosity, conspiracy beliefs, trust, national identification, perceived effectiveness, and quality of institutions (7)(8)(9)(10)(11)(12)(13)(14). In this paper, we argue that in order to understand why people support or oppose certain measures, it is crucial to understand (I) which individuals, groups, social movements, or organizations (referred to as 'protagonists' in the following) people identify as relevant and (II) how they are evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…We also performed post hoc power assessments using the R package “semPower” to quantify the achieved power of our structural equation modeling (Dong et al, 2021; Moshagen & Erdfelder, 2016). On the basis of the parameters of our baseline model (e.g., df = 224, Root Mean Squared Error of Approximation = .08 in the model predicting outgroup trust), a sample size of N = 528 yielded a power >99.99% to reject an incorrect model at an α level of .05.…”
Section: Methodsmentioning
confidence: 99%
“…Here, the self-interests of the individuals following or breaking the rules are key. That is individuals' self-interests defined by an initial behaviour (i.e., the a priori behaviour expressed without an external constraint; [47][48][49][50][51]). In some individuals, this initial behaviour persists after a rule is present [23].…”
Section: Spontaneous Deliberative Rule-breakingmentioning
confidence: 99%